Tingkat Pengangguran Terbuka Periode Sebelum hingga Sesudah Pandemi Covid-19 dengan Pendekatan Non-Parametrik - Mayapada, Retno; Fardinah, Fardinah (ESTIMATOR : Journal of Applied Statistics, Mathematics, and Data Science, 2024)
The unemployment rate is one of the factors related to a country's economy. During the COVID-19 pandemic, there was a decline in economic growth in Indonesia which also had a negative impact on the labor market. The decreased mobility of people causes reduced economic activity and ultimately the number of poverty increases. This research compares the percentage of unemployment rates in Indonesia in the period before, during, and after the COVID-19 pandemic using a non-parametric approach because the data of unemployment rates in 2020 and 2021 are not normally distributed. The non-parametric tests used in this research are the Friedman test and the Nemenyi post-hoc test. Based on research conducted, it was found that there was a statistically significant difference (?=5%) between the percentage of unemployment rates during the COVID-19 pandemic and the period before and after the COVID-19 pandemic. Meanwhile, the difference between before and after COVID-19 occurred was not statistically significant (?=5%). However, the average unemployment rate in 2023 is the smallest that compared to previous years. This shows that the economy in Indonesia is slowly starting to improve after the COVID-19 pandemic.